(untitled) (Research, Society and Development, 2020)
The validation of reference genes is an essential step for any RT-qPCR analysis. In this way, the present paper aimed to identify and validate reference genes for RT-qPCR in cardiac tissue of rats of the Rattus norvegicus albinus specie, submitted to obesity associated or not to type 2 diabetes mellitus. For this, the metabolic changes were induced at the 42nd day of life and the euthanasia was performed on the 70th day. The heart apexes were collected and destinates for RNA extraction. The RT-qPCR technique was performed in own thermocycler, the efficiency of the primers found by the LinReg software and the stability of the expression of the reference genes in the samples was analyzed by the RefFinder algorithm. The candidates for reference genes were GAPDH, POLR2A, RPL32, and RPL4 and the target gene used to verify the differences in gene expression of candidates for reference genes was CMA1. The obese animals showed a decrease in CMA1 gene expression when compared to the two most stable reference genes. The opposite occurs when it is compared to the two less stable reference genes. The GAPDH and POLR2A genes are the best to normalize the reactions with the samples in question. There is no universal reference gene for all situations, which requires systematic validation for each situation. The use of unvalidated reference genes may compromise the interpretation of the expression of the target genes, which would prevent the reflection of the actual situation.